Etude de l’effet de la tisane de persil (Petroselinum sativum) sur les paramètres biochimiques chez les lithiasiques - Fellouh, Sarah; Ouahba, Ahlam (My University, 2022)
Urinary lithiasis is an increasingly frequent pathology, with various causes. Because of the importance of plants in the traditional treatment of several diseases, we studied the effect of parsley (Petroselinum sativum) tea on crystalluria and some biochemical parameters (urea, creatinine, uric acid, calcium, Na, K, CI) in stone formers. The tea was prepared by pouring one liter of hot water over 150 to 200 g of fresh parsley, which was infused and then consumed by the patients at a rate of one glass per day, during 07 days. The study involved 14 stone formers aged 28 to 79 years (mean 51 years), with a sex ratio M/F of 1.33 while the most frequent type of calculus is type Ia, whose composition is calcium oxalate monohydrate or whewellite. The study of Cristalluria showed that after the consumption of parsley tea, the size and number of crystals and aggregates decreased significantly. Also, there was a very important correction of the biochemical parameters and those of the ionogram; the values approached the norms in the patients after the consumption of the tea. This shows the beneficial effect of parsley tea on the biochemical parameters, preventing a recurrence among stone formers.
Keywords: Urinary lithiasis; biochemical parameters; crystalluria; ionogram; parsley tea (Petroselinum sativum)